The Development of Learning Based on Social Emotional Learning (SEL) Design - Adiska Nur; Ayu Mukti Sari; Zahwa Nurmalita Adityas; Riris Eka Setiani (The Future of Education Journal, 2026)
This study is motivated by the educational challenges of the 21st century, which require the strengthening of not only cognitive but also social-emotional aspects of students, particularly in Islamic Religious Education (IRE) instruction, which still tends to be text-based. The objective of this study is to examine the concepts and theoretical foundations of Social-Emotional Learning (SEL), identify the principles of SEL-based instructional design, and formulate a conceptual model for its implementation in PAI instruction. This study employs a qualitative method with a descriptive approach through a systematic literature review, utilizing scientific articles, journals, and educational documents related to SEL. Data were collected through documentation techniques and analyzed using content analysis, including data reduction, categorization, synthesis, and conclusion drawing. The results indicate that SEL has strong relevance in 21st-century learning as it develops social-emotional competencies that support 4C skills. The integration of SEL into Islamic Religious Education aligns with Islamic moral values such as self-reflection (muhasabah), patience (sabar), and brotherhood (ukhuwah), and contributes positively to students' psychological well-being, learning motivation, and social interaction quality. Thus, SEL-based instructional design serves as a strategic approach in shaping students who are well-rounded, adaptive, and of strong character.